Childhood sexual and physical abuse: age at exposure modulates impact on functional outcome in early psychosis patients. Issue 13 (24th April 2015) - Alameda, L.; Ferrari, C.; Baumann, P. S.; Gholam-Rezaee, M.; Do, K. Q.; Conus, P.
Abstract : Background: Evidence suggests a relationship between exposure to trauma during childhood and functional impairments in psychotic patients. However, the impact of age at the time of exposure has been understudied in early psychosis (EP) patients. Method: Two hundred and twenty-five patients aged 18–35 years were assessed at baseline and after 2, 6, 18, 24, 30 and 36 months of treatment. Patients exposed to sexual and/or physical abuse (SPA) were classified according to age at the time of first exposure (Early SPA: before age 11 years; Late SPA: between ages 12 and 15 years) and then compared to patients who were not exposed to such trauma (Non-SPA). The functional level in the premorbid phase was measured with the Premorbid Adjustment Scale (PAS) and with the Global Assessment of Functioning (GAF) scale and the Social and Occupational Functioning Assessment Scale (SOFAS) during follow-up. Results: There were 24.8% of patients with a documented history of SPA. Late SPA patients were more likely to be female ( p = 0.010). Comparison with non-SPA patients revealed that: (1) both Early and Late SPA groups showed poorer premorbid social functioning during early adolescence, and (2) while patients with Early SPA had poorer functional level at follow-up with lower GAF ( p = 0.025) and lower SOFAS ( p = 0.048) scores, Late SPA patients did not. Conclusion: Our results suggest a link between exposure to SPA and the later impairment of social functioning before the onset of the disease. EP patients exposed to SPA before age 12 may present long-lasting functional impairment, while patients exposed at a later age may improve in this regard and have a better functional outcome.